Neighbourhood Team Development to promote resident centred approaches in nursing homes: a protocol for a multi component intervention - Veronique M. Boscart; Souraya Sidani; Jenny Ploeg; Sherry L. Dupuis; George Heckman; Jessica Luh Kim; Josie d'Avernas; Paul Brown (BMC, 2019)
Abstract Background As the demand for nursing home (NH) services increases, older adults and their families expect exceptional services. Neighbourhood Team Development (NTD) is a multi-component intervention designed to train team members (staff) in the implementation of resident-centered care in NH settings. A neighbourhood is a 32-resident home area within a NH. This paper presents the protocol used to implement and evaluate NTD. The evaluation aimed to 1) examine fidelity with which the NTD was implemented across NHs; 2) explore contextual factors associated with implementation and outcomes of the NTD; and 3) examine effects of NTD on residents, team members, family, and organizational outcomes, and the association between level of implementation fidelity and outcomes. Methods The study employed a repeated measure, mixed method design. NTD consisted of a 30-month standardised training and implementation plan to modify the physical environment, organize delivery and services and align staff members to promote inter-professional team collaboration and enhanced resident centeredness. Training was centred in each 32-resident neighbourhood or home area. Quantitative and qualitative data were collected with reliable and valid measures over the course of 3 years from residents (clinical outcomes, quality of life, satisfaction with care, perception of person centeredness, opportunities for social engagement), families (satisfaction with care for relative, person centeredness, relationship opportunities), team members (satisfaction with job, ability to provide person centered care, team relationships) and organizations (retention, turnover, staffing, events) in 6 NHs. Mixed models were used for the analysis. Discussion The advantages and limitations of the NTD intervention are described. The challenges in implementing and evaluating this multi-component intervention are discussed as related to the complexity of the NH environment. Trial registration ClinicalTrials.gov ID: NCT03415217 (January 30, 2018 - Retrospectively registered).